Association of time in range, as assessed by continuous glucose monitoring, with painful diabetic polyneuropathy - Yang, Junpeng; Yang, Xueli; Zhao, Dongni; Wang, Xiaobing; Wei, Wei; Yuan, Huijuan (Journal of diabetes investigation, 2021)
Aims/Introduction This study aimed to evaluate the association between time in range (TIR) obtained from continuous glucose monitoring and the prevalence and degree of painful diabetic neuropathy. Materials and Methods A total of 364 individuals with diabetic peripheral neuropathy were enrolled in this study. Sensor‐based flash glucose monitoring systems were used to monitor the participants’ glucose levels, and the glycemic variability metrics were calculated, including the TIR, glucose coefficient of variation, standard deviation and the mean amplitude of glycemic excursions. The participants were asked to record any form of pain during the 2 weeks of monitoring, and score the pain every day on a numerical rating scale. Based on the numerical rating scale, the patients were divided into the pain‐free group, mild pain group and moderate/severe pain group. Results Overall, 51.92% (189/364) of the participants were diagnosed with painful diabetic neuropathy. Compared with the pain‐free group, the level of TIR decreased significantly in the mild pain and moderate/severe pain groups (P < 0.05). The prevalence of mild pain and moderate/severe pain decreased with increasing TIR quartiles (all P < 0.05). Multiple linear regression analysis showed that TIR was significantly negatively correlated with the numerical rating scale score after adjustment for glycated hemoglobin, glycemic variability indicators and other risk factors (P < 0.05). Logistic regression analysis showed that a decreasing level of TIR was significantly associated with an increasing risk of any pain and moderate/severe pain (P < 0.05). Conclusions TIR is correlated with painful diabetic neuropathy and is underscored as a valuable clinical evaluation measure. Time in range is correlated with the degree of painful diabetic neuropathy independently of the glycated hemoglobin level, other glycemic variability metrics and risk factors among diabetes patients. Furthermore, time in range was a valuable clinical evaluation indicator for patients with diabetes.